High throughput biophysical profiling of neutrophils using microfluidics impedance cytometry - Thannirmalai, Arunachalam (Nanyang Technological University, 2024)
The study of biophysical cell properties including mechanical and electrical characteristics of different cell components in diseases has paved the way for novel avenues in pathology investigation and clinical diagnostics. Conventional biomechanical and electrophysiology techniques are unsuitable for clinical applications as they are labour-intensive and require large sample volumes. To address these challenges, our group has previously developed a novel high-throughput (~3000 cells per minute) label-free microfluidics impedance cytometry to measure single-cell electrical and mechanical properties based on multi-frequencies (0.3 to 12 MHz) impedance measurements. The aim of this project was to evaluate this novel technique’s application for risk stratification of cardiovascular diseases (CVDs) in type 2 diabetes mellitus using neutrophils, a key effector cell of the innate immunity, isolated from whole blood. Healthy neutrophils were treated in vitro with high glucose (30 mM), oxidized lipoproteins (oxLDL) and inflammatory cytokines (TNF-α) to assess their biophysical changes based on impedance signatures. Next, whole blood was treated with platelet agonist (TRAP-6) to stimulate the formation of neutrophil-platelet aggregates (NPAs) and monocyte-platelet aggregates (MPAs) which are pathological markers in atherosclerosis. Using an unsupervised dimensional reduction technique namely Uniform Manifold Approximation and Projection (UMAP), label-free quantification of cell aggregates based on their biophysical properties measured utilising impedance cytometry was demonstrated, which showed good correlation with antibodies-based flow cytometry analysis. Overall, the microfluidic impedance cytometry device showed great potential in accurately measuring single-cell biophysical properties at high throughputs, and further in vivo and clinical verifications are recommended for future works.